Understanding organized crime - Mallory, Stephen L. (Criminal justice illuminated, 2007)
An introduction to organized crime : definitions and distinctions -- Evolution of organized crime and the impact on investigative -- Strategies and law enforcement -- Why organized crime continues to exist -- Drug trafficking organizations of Colombia -- The Mexican cartels -- The Russian mafia -- The Italian American mafia -- The Yakuza -- Triads and tongs -- American outlaw motorcycle gangs -- Hispanic and African American gangs -- Major statutes, legislations, and methods of organized crime -- Investigations -- The intelligence function and its application to organized crime -- Where do we go from here?